Applications of discrete mathematics - Michaels, John G. (McGraw-Hill, 1992)
This book presents a wide variety of interesting applications of discrete mathematics in a flexible and accessible format. They are arranged in three sections: discrete structures and computing; combinatorics,; and graph theory